Air pollution and preterm birth: A time‐stratified case‐crossover study in the San Joaquin Valley of California - Ha, Sandie; Martinez, Valerie; Chan‐Golston, Alec M. (Paediatric and perinatal epidemiology, 2022)
Background Air pollution is linked to preterm birth (PTB), but existing studies are primarily focused on chronic exposures, conducted in areas with moderate pollution, and/or subject to confounding. Objectives We investigated short‐term associations between two pollutants [particulate matter <2.5 microns (PM2.5) and ozone] and PTB, and estimated excess PTB cases potentially attributed to these pollutants. Methods This time‐stratified case‐crossover study includes 196,970 singleton pregnancies affected by PTB and early term birth from the San Joaquin Valley (SJV), California, USA (2007–2015). Daily ozone and PM2.5 concentrations were estimated by the SJV Air Pollution Control District and geospatially linked to maternal zip code. We used conditional logistic regression models to estimate the odds ratio (OR) and 95% confidence intervals (CI) for the associations between an interquartile range (IQR) increase in pollutants and very preterm (VPTB, 20–34 weeks), moderate preterm (MPTB, 34–36 weeks) and early term births (ETB, 37–38 weeks). We adjusted all models for co‐pollutants and meteorological factors. Results During warm seasons (May‐October), an IQR increase in ozone was associated with 9–11% increased odds of VPTB from lag 0 (ORlag0 1.09, 95% CI 1.04,1.16) to lag 7 (ORlag7 1.11, 95% CI 1.04,1.16). Findings were consistent for MPTB and ETB. Ozone was potentially responsible for an excess of 3–6 VPTBs, 7–9 PTBs and 24–42 ETBs per 1,000 singleton deliveries. During cold seasons (November‐April), increased PM2.5 exposure was associated with 5–6% increased odds of VPTB beginning at lag 3 (ORlag3 1.06, 95% CI 1.02,1.11). PM2.5 was associated with an excess of 1–3 VPTBs, 0–3 MPTBs and 6–18 ETBs per 1,000 singleton deliveries. Conclusions PM2.5 and ozone are associated with increased risk of VPTB, MPTB and ETB within one week of exposure and are potential contributors to the increasing PTB trend. More research is needed to further understand the role of air pollution on PTB risk.